EFL Students’ Reader Response-driven Self-reflection Strategy in Learning Literature - Monica; R. Bunga Febriani; Iskhak (International Journal of Innovation and Education Research, 2023)
This study aimed to observe students’ self-reflection activities are evident in the classroom to stimulate critical reading activities.. The study used a qualitative case study method in the process of data taken from observation. The participant of this study was chosen purposively which was 15 students second-level of English Education Program at one of the Universities in Ciamis who was observed. The result of this study revealed that it can be seen that there are reflection activities through reader response in the literature class, students are encouraged to read critically. This study concludes that the used of reflection through reader response in digital literature learning is effective in use and can stimulate critical reading activities.